185 Remodelling of Specialised Domains of the Sarcolemma in Heart Failure; Reorganisation of the Intercalted Disc Revealed by Nano-scale Imaging. (31st May 2014) - Pinali, Christian; Bennett, Hayley J; Davenport, J Bernard; Caldwell, Jessica L; Trafford, Andrew W; Kitmitto, Ashraf
Abstract : Introduction: The sarcolemma is a highly specialised organelle of the cardiac myocyte. In addition to forming the envelope of the cell its organisation into specialised domains (transverse tubules, TT) is central for calcium influx and facilitation of mechanical, electrical and chemical coupling (intercalated disc, ICD) between myocytes. We have previously used serial block face scanning electron microscopy (sbfSEM) for the three-dimensional reconstruction (3-D) of the TT network revealing remodelling in an ovine model of heart failure (HF). We have hypothesised that in HF there is also remodelling of the ICD. However, to-date there are no high resolution 3-D structures for an ICD. Current knowledge of the ICD organisation is derived from two-dimensional transmission electron microscopy images. In this study we have applied sbfSEM for the first 3-D morphological analysis of the ICD structure in healthy and failing cells. Methods: Samples were taken from the left ventricle (LV) of tachypacing induced HF control sheep (n = 4). Sheep were killed with an overdose of pentobarbitone (200mg/kg iv). All procedures were carried out in accordance to the United Kingdom Animals (Scientific Procedures) Act of 1986 and the University of Manchester's ethical review process. Samples were prepared as described previously. Blocks of fixed tissue were imaged using an FEI Quanta 250 FEG SEM equipped with a Gatan 3View system. 3-D information through the block was generated at 15, 15, 50 nm (X, Y, Z) resolution at the pixel level. Images were segmented in Fiji or IMOD. Frozen tissue was lysed using RIPA buffer and protein profiles analysed by western blotting. Results: We report the first high resolution 3-D structure of entire ICDs in situ in the LV of healthy and failing hearts leading to the identification and quantification of structural remodelling. The amplitudes of the plicae are four-fold greater in the failing cells ( P < 0 .01) compared to control. These morphological adaptations are accompanied by an up-regulation of desmin and the N-cadherin/catenin complex involved in stabilising the end-to-end myocyte adhesive and mechanical properties. We also identified vacuoles within the extracellular space and larger vacuoles within the cells that associate with each side of the ICD. Conclusions: Our data reveal how the failing heart adapts to the increased mechanical stress from the tachypacing by remodelling both the structural and protein properties of the ICD. We suggest that the vacuoles formed between the ICD leaflets may in part be due to the loss of gap junctions but that the larger vacuoles are a result of mitochondrial rupture. We have characterised in 3-D the features of control ICDs revealing a consistency in morphological features and therefore, we propose that the remodelling and extent of the rearrangement may have applications for differentiating between healthy and disease phenotypes and also as a measure of disease progression.